Posttraumatic Stress Symptoms and Posttraumatic Growth in Mothers of Children With Intellectual Disability – The Role of Intrusive and Deliberate Ruminations: A Preliminary Report - Kiełb, Katarzyna; Bargiel-Matusiewicz, Kamilla M.; Pisula, Ewa (Frontiers in Psychology, 2019)
Background: The aim of this study was to find out if mothers of children with intellectual disability demonstrate symptoms of posttraumatic stress and posttraumatic growth, and to define the role of intrusive and deliberate ruminations in this area. Method: The questionnaire-based study included 85 mothers of children with intellectual disability. Three standardized questionnaires were used: Impact of Event Scale-Revised, Posttraumatic Growth Inventory, Event-Related Rumination Scale. Results: Relative to the population norm in Poland, 52% of mothers of children with intellectual disability demonstrated at least moderate level of symptoms of posttraumatic stress. The mean level of posttraumatic growth was high in this group. Intrusive ruminations and mothers’ age served as a predictor for posttraumatic stress symptoms. None of the types of rumination correlated with posttraumatic growth. Conclusions: Mothers of children with intellectual disability demonstrated symptoms of both posttraumatic stress and posttraumatic growth. Intrusive ruminations proved to be significant predictors for posttraumatic stress symptoms.